Comparative study on quality characteristics of sweet Huangjiu from different regions in China - YI Zongwei, GUO Zhuang, JIANG Zaiming, WANG Yurong, HOU Qiangchuan (Zhongguo niangzao, 2025)
In this study, the color, physicochemical properties, flavor, and taste of 21 representative sweet Huangjiu samples from 6 major Huangjiu production regions in China were systematically analyzed using national standard detection methods combined with modern analytical techniques. The results showed that the overall quality of sweet Huangjiu from Fangxian, Hubei province showed the greatest differences compared to other regions. Specifically, in terms of color, sweet Huangjiu from Fangxian, Hubei province exhibited the highest brightness, sweet Huangjiu from Longyan, Fujian province displayed the most vibrant red hue, while sweet Huangjiu from Shaoxing, Zhejiang province presented the deepest yellow color. Regarding flavor and taste, sweet Huangjiu from Fangxian, Hubei province had the highest response values to W3C (aromatic compounds), W1S (short-chain alkanes) and W5S (nitrogen oxides) (P<0.05), whereas sweet Huangjiu from Qingdao, Shandong province had significantly higher bitterness, astringency and bitter aftertaste than sweet Huangjiu from Fangxian, Hubei province and Shaoxing, Zhejiang province (P<0.05). In terms of physicochemical qualities, the contents of total sugar and soluble solids in sweet Huangjiu from Zhenjiang, Jiangsu province and Heyuan, Guangdong province were higher (P<0.05). Sweet Huangjiu from Shaoxing, Zhejiang province was rich in amino acids, while sweet Huangjiu from Heyuan, Guangdong province possessed the highest alcohol content. The main distinguishing factors among sweet Huangjiu from different regions were identified as follows: aromatic compounds and L* value of sweet Huangjiu from Fangxian, Hubei province; alcohol content, total sugar, and soluble solids of sweet Huangjiu from Heyuan, Guangdong province and Zhenjiang, Jiangsu province; taste of sweet Huangjiu from Qingdao, Shandong province and Longyan, Fujian province, and a* value, amino acid nitrogen, W2W (aromatic compounds and organic sulfides), and W3S (long-chain alkanes) of sweet Huangjiu from Shaoxing, Zhejiang province.